2022
DOI: 10.1093/ageing/afac013
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, knowledge and attitudes about COVID-19 vaccine hesitancy in older Portuguese adults

Abstract: Background Coronavirus 2019 (COVID-19) has become a public-health emergency of international concern. Most efforts to contain the spread and transmission of the virus rely on campaigns and interventions targeted to reduce Vaccine Hesitancy and Refusal (VHR). Objective this study aims to assess the major factors associated with VHR in the older population in Portugal. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
3
20
2
Order By: Relevance
“…However, contrarily to previously published literature, 16 the results of our study indicate that VH among health professionals is equal to or greater than in the general population, 29 , 30 with a high prevalence of VH of almost 20% among physicians, and around 10% in the other health professionals, which might be related to a higher number of concerns regarding these vaccines than other populations, such as older adults. 29 The results of our study indicate that VH is very strongly influenced by perceptions, beliefs and attitudes. 31 As these factors are modifiable, this study may support the development of communication and intervention strategies designed to change them, thus reducing VH.…”
Section: Discussionsupporting
confidence: 59%
“…However, contrarily to previously published literature, 16 the results of our study indicate that VH among health professionals is equal to or greater than in the general population, 29 , 30 with a high prevalence of VH of almost 20% among physicians, and around 10% in the other health professionals, which might be related to a higher number of concerns regarding these vaccines than other populations, such as older adults. 29 The results of our study indicate that VH is very strongly influenced by perceptions, beliefs and attitudes. 31 As these factors are modifiable, this study may support the development of communication and intervention strategies designed to change them, thus reducing VH.…”
Section: Discussionsupporting
confidence: 59%
“…Vaccine hesitancy is described as the reluctance or refusal to vaccinate despite the availability of vaccines ( Beleche et al, 2021 ; Silva et al, 2022 ). Vaccine hesitancy is usually caused by doubts, distrust, and worries or fears concerning vaccine efficacy, protection, and safety.…”
mentioning
confidence: 99%
“…It has been shown that the use of social media and the launch of public health promotion campaigns have great potential for the target audience [217]. Compared to other methods, launching campaigns on different platforms of social media amplifies bi-directional communication and efficiently leads to changes in the user's behavior [124,218,219].…”
Section: Merging Strategiesmentioning
confidence: 99%